Social media in Southeast Italy : crafting ideals - Nicolescu, Razvan (Why we post., 2016)
Why is social media in southeast Italy so predictable when it is used by such a range of different people? This book describes the impact of social media on the population of a town in the southern region of Puglia, Italy. Razvan Nicolescu spent 15 months living among the town's residents, exploring what it means to be an individual on social media. Why do people from this region conform on platforms that are designed for personal expression? Nicolescu argues that social media use in this region of the world is related to how people want to portray themselves. He pays special attention to the ability of users to craft their appearance in relation to collective ideals, values and social positions, and how this feature of social media has, for the residents of the town, become a moral obligation: they are expected to be willing to adapt their appearance to suit their different audiences at the same time, which is crucial in a town where religion and family are at the heart of daily life.